Comparison of endoscopic techniques designed for posterior glottic stenosis-A cadaver morphometric study - Sztanó Balázs (LARYNGOSCOPE, 2014)
OBJECTIVES/HYPOTHESIS: Posterior glottic stenosis may cause more or less severe dyspnea. The popular endoscopic procedures have only a limited role in the treatment. Considering our clinical experiences, endoscopic arytenoid abduction lateropexy (EAAL) after proper mobilization of the fixed joints provides an effective option even in high-grade stenoses. STUDY DESIGN: To confirm these clinical observations, a morphometric study was performed in 100 cadaver larynges (50 male, 50 female) to objectively compare the endoscopic glottis-widening procedures. METHODS: The postoperative measurements of the posterior commissure following EAAL, classic vocal cord laterofixation (VCL), transverse cordotomy (TC), and arytenoidectomy (AE) were assessed by a digital image analyzer program. The distance between the vocal process of the lateralized vocal fold and the midline, the angle between the axis of the posterior commissure midpoint, and the vocal process and laryngeal median sagittal line were measured. RESULTS: EAAL was found to be more effective in improving the posterior glottis configuration; however, AE and VCL were beneficial as well. CONCLUSIONS: Our morphometric study proved that organ-preserving EAAL provided more space in the posterior glottic area. Fibrous reconnection and contraction of the scar can be minimized in this way, which may be the clinical efficacy explanation. LEVEL OF EVIDENCE: N/A. Laryngoscope, 2013.